PENGEMBANGAN MODUL PEMBELAJARAN KONDISIONAL UNTUK BELAJAR DARI RUMAH (BDR) - Revita Yuni; Roni Afriadi (Universitas Negeri Medan, 2020)
Abstract:.Development of Conditional Learning Module of BDR. Learning requires two-way communication between educators and students so that all learning activities and learning objectives can be channeled properly. Therefore, to achieve the goals of national education, synergies are needed in various sectors to support education. During this pandemic, of course, all fields experience difficulties, including in the field of education. Covid-19 has resulted in fundamental policy changes in the world of education. Through Circular no. 4 of 2020 from the Minister of Education and culture which recommends that all activities in educational institutions must maintain a distance and all material delivery will be delivered from their respective homes. It is hoped that online and offline learning can be an alternative so that learning can be carried out in the midst of the current pandemic situation. For areas that have a good internet network, they can carry out the teaching and learning process in a network (online) well. Meanwhile, for areas where the internet network is inadequate, learning is carried out outside the network (offline). In learning outside the network, the teacher prepares LKPD and on certain days students come to school to collect their assignments and students receive new assignments for the next week. So learning is only a task so that assignments are not maximally conveyed. As a result, there is a lack of interaction and misunderstanding between teachers and students is not uncommon. One of the offline learning solutions (offline) during the Covid-19 pandemic is a conditional module which students can use independently. Learning with the module, students can feel the presence of the teacher as if learning in class is active and fun. The research method used by researchers is the Research and Development (R&D) method of research and development. This research is research that is used to produce certain products, and to test the effectiveness of these products. At the development stage, the modules that have been designed are evaluated or validated by material experts and media experts. Keywords: offline learning, Learning from home and modulesAbstrak: Pengembangan modul pembelajaran kondisional untuk BDR. Pembelajaran membutuhkan komunikasi dua arah antara pendidik dengan peserta didik agar segala kegiatan pembelajaran dan tujuan pembelajaran dapat tersalur dengan baik. Oleh karena itu, untuk mencapai tujuan pendidikan nasional dibutuhkan sinergi dalam berbagai sektor dalam mendukung pendidikan. Pada masa pandemi ini, tentunya semua bidang mengalami kesulitan termasuk dalam bidang pendidikan. Covid-19 ini mengakibatkan terjadinya perubahan kebijakan secara mendasar dalam dunia pendidikan. Melalui Surat Edaran no. 4 tahun 2020 dari Menteri Pendidikan dan kebudayaan yang menganjurkan seluruh kegiatan di institusi pendidikan harus jaga jarak dan seluruh penyampaian materi akan disampaikan dari rumah masing-masing. Pemberlakuan pembelajaran secara daring dan luring diharapkan dapat menjadi alternatif agar tetap terlaksana pembelajaran di tengah situasi pandemi saat ini. Bagi daerah yang memiliki jaringan internet bagus dapat melakukan proses belajar mengajar dalam jaringan (daring) dengan baik. Sedangkan bagi daerah yang jaringan internet tidak memadai, pembelajaran dilakukan di luar jaringan (luring). Pada pembelajaran di luar jaringan guru menyusun LKPD dan pada hari tertentu siswa datang kesekolah mengumpulkan tugasnya dan siswa menerima tugas yang baru untuk satu minggu kedepan. Jadi pembelajaran hanya sebatas tugas sehingga penugasan tidak tersampaikan secara maksimal. Akibatnya kurangnya interaksi dan tak jarang terjadi kesalahpahaman antara guru dengan siswa. Salah satu solusi pembelajaran luring (luar jaringan) di masa pandemi covid-19 ini adalah modul yang sifatnya kondisional yang mana dapat digunakan siswa secara mandiri. Belajar dengan modul siswa dapat merasakan kehadiran guru seperti belajar di kelas secara aktif dan menyenangkan. Metode penelitian yang digunakan peneliti adalah metode penelitian dan pengembangan Research and Development (R&D). Penelitian ini adalah penelitian yang digunakan untuk menghasilkan produk tertentu, dan menguji keefektifan produk tersebut. Pada tahap pengembangan, modul yang telah didesain dilakukan penilaian atau validasi oleh ahli materi dan ahli media. Kata kunci: pembelajaran luring, BDR dan modul